-g+17=-(g-17)

Simple and best practice solution for -g+17=-(g-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -g+17=-(g-17) equation:


Simplifying
-1g + 17 = -1(g + -17)

Reorder the terms:
17 + -1g = -1(g + -17)

Reorder the terms:
17 + -1g = -1(-17 + g)
17 + -1g = (-17 * -1 + g * -1)
17 + -1g = (17 + -1g)

Add '-17' to each side of the equation.
17 + -17 + -1g = 17 + -17 + -1g

Combine like terms: 17 + -17 = 0
0 + -1g = 17 + -17 + -1g
-1g = 17 + -17 + -1g

Combine like terms: 17 + -17 = 0
-1g = 0 + -1g
-1g = -1g

Add 'g' to each side of the equation.
-1g + g = -1g + g

Combine like terms: -1g + g = 0
0 = -1g + g

Combine like terms: -1g + g = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2y+2=24-26 | | w-4.4=9.6 | | 5/6*c-2/3*c=1/3 | | w-4.4=9.7 | | 5c+10=4c-8 | | x-8y=-20 | | f(9a)=x+1 | | 5/6-(-3/4) | | 42j+18-19j=-46 | | 2(x-2y)=18 | | 8-(4n-3)=9-5n | | 3v+8=2(v+4)+v | | 39+7k=8[k+4] | | -9+(-32)-15+6= | | 2x-(12-x)=x+7+2x | | A=1/2x22x7 | | .50=lny | | M/pi=3 | | -38-7k=8(k+4) | | 3=q | | x+3/5=-6 | | t+75=-225 | | 9/16-5/12 | | x/3-7=7 | | 7(x+8)=3(x+2)+4x | | x/20-1/5=35 | | 3x+5=-7x-2q | | log[5](15x+5)-log[5](x)=2 | | -68=-20-8r | | 6-m/8=20 | | 50+2x=100 | | ((x^2)-(2x))=15 |

Equations solver categories